MODELLING OF DOMESTIC WATER DEMAND USING SPATIAL DATA POPULATION FOR CISADANE UPSTREAM WATERSHED - Dina Paramitha Anggraeni Hidayat; Yuddi Yudistira (INDONESIAN JOURNAL OF CONSTRUCTION ENGINEERING AND SUSTAINABLE DEVELOPMENT (CESD), 2018)
In Indonesia, water resources management planning has done based on river area. But the problem is the calculation still based on population data with administrative boundary. This is caused by the lack of population data with watershed or river area boundary. Geographical Information System (GIS) is a tools to analyze, visualize and interpret data with spatial and geographic data. For this research, GIS is used to generate population data with watershed and river area boundary,then the result will used for domestic water demand calculation for Cisadane upstream watershed. For all district in Cisadane Upstream Watershed, the largest district in entire watershed are Cibungbulang, Leuwiliang and Nanggung. But the most dense population are Ciomas, Ciampea and Cibungbulang. The calculation using watershed boundary resulting significant difference from district boundary. With spatial data population using watershed boundary, domestic water demand calculation result can be more accurate than using all district population data.